BALI-BALIKU BEACH FRONT LUXURY VILLAS’ RECEPTIONIST UDERSTANDING OF STANDARD OPERATING PROCEDURES - I Putu Dede Sukadana Putra; Lien Darlina; I Ketut Suarta (Journal of Applied Sciences in Travel and Hospitality, 2018)
This paper aims to find out how much receptionist staff understandi standard operating procedure (SOP) in Bali-Baliku Beach Front Luxury Villas. This paper was made because of the interest of the writer about the changes that occurred after the implementation of standard operating procedure (SOP) in Bali-Baliku Beach Front Luxury Villas considering that the standard operational procedure is an important thing in a company as a document or tool to achieve company goals. This research uses descriptive qualitative research method. Methods of data collection in this study are interviews, observations, questionnaires, and literature study. The results of this study indicate that: 1) All employees of the receptionist have done their duties and responsibilities in implementing standard operating procedures (SOP) very well and correctly, in accordance with the direction of the front office superiors in Bali Baliku Beach Front Luxury Villas. 2) All employees of the receptionist have a good understanding of the definition of operational standard procedures and can define them. 3) All receptionist employees have understood and implemented the stages in serving the guests such as the stages of serving the guest check-in, serving the check-out guest, informing the porter service, posting guest payments, doing print out registration cards, scanning guest id, settle cash payment, and settle payment by credit card properly and in accordance with SOP applicable in receptionist section.